Renewing criminalized and hegemonic cultural landscapes - Cayli, Baris (Critical criminology, 2014)
The Mafia’s long historical pedigree in Mezzogiorno, Southern Italy, has empowered the Mafioso as a notorious, uncontested, and hegemonic figure. The counter-cultural resistance against the mafiosi culture began to be institutionalized in the early 1990s. Today, Libera Terra is the largest civil society organization in the country that uses the lands confiscated from the Mafia as a space of cultural repertoire to realize its ideals. Deploying labor force through volunteer participation, producing biological fruits and vegetables, and providing information to the students on the fields are the principal cultural practices of this struggle. The confiscated lands make the Italian experience of anti-Mafia resistance a unique example by connecting the land with the ideals of cultural change. The sociocultural resistance of Libera Terra conveys a political message through these practices and utters that the Mafia is not invincible. This study draws the complex panorama of the Mafia and anti-Mafia movement that uses the ‘confiscated lands’ as cultural and public spaces for resistance and socio-cultural change. In doing so, this article sheds new light on the relationship between rural criminology and crime prevention policies in Southern Italy by demonstrating how community development practice of Libera Terra changes the meaning of landscape through iconographic symbolism and ethnographic performance.